Mower County Aerial Survey 1949 Adams Townships Sections 1, 2, 11 and 12; 3f89 (Mower County Historical Society, 1303 Sixth Avenue SW, Austin, MN 55912; www2.smig.net/mchistory)
d7d7b9de1af496918434eca1913ab51a
United States
Minnesota
Mower
Adams Township; Adams
Little Cedar River
Keywords: Adams Township Sections 1, 2, 11 and 12; County Road 7; State Highway 56; Sacred Heart Catholic Cemetery; Sacred Heart Catholic Church; Chicago, Milwaukee and St. Paul Railroad; agriculture; business district; Agriculture